DINAMIKA KELIMPAHAN ORIBATIDA PADA AREA PERKEBUNAN KELAPA SAWIT DI KECAMATAN BAJUBANG BATANGHARI JAMBI - Yuni Lisafitri; Rahayu Widyastuti; Dwi Andreas Santosa (Jurnal Ilmu Tanah dan Lingkungan, 2015)
Oribatids are one of the important fauna groups in the soil. They have an important role in the decomposition of organic matter in the soil. The objection of this research was to study population dynamics of Oribatids through determining the abundance and diversity of Oribatids and to know the effect of environmental factors on Oribatids in oil palm plantation at Bajubang, Batanghari, Jambi. Soil and litter samples were taken from four different locations (25 m x 25 m) and from each location three samples were taken from litter lanes and open lanes, respectively (the size was 16 x 16 cm with a depth of soil is 5 cm). The samples were extracted using Kempson extractor. Identification of Oribatids was done to the family level and the diversity of Oribatids was measured using Shannon’s diversity index. The population dynamic of Oribatids showed a fluctuation in the sampling period. When rainfall increased >200 mm did not follow by increasing abundance and diversity (number of the family) of Oribatid mites. When rainfall between 100 – 200 mm was the optimal condition for Oribatids so abundance and diversity (the number of the family) of Oribatids increased. But, when rainfall <100 mm especially in February 2014 (the lowest rainfall 1 mm), abundance and diversity (number of the family) of Oribatids was lowest (330 individual m-2; 7 families) compared to another month. It was assumed that Oribatids may migrate into the deep soil to avoid a harsh environmental condition. Abundance and diversity (number of the family) of oribatids were significantly higher in litter lanes (4,560 individual m-2; 25 families) than in open lanes (1,570 individual m-2; 14 families). The availability of litter in the litter lanes was higher than in open lanes. In this research, There are 3 families that most abundance and always found on the sampling period, they are Scheloribatidae, Mycobatidae and Galumniidae. Keywords: Abundance, diversity, oil palm plantation, Oribatids, soil fauna